Analisis Faktor Risk Profile, Good Corporate Governance, Earnings, dan Capital terhadap Profitabilitas pada Bank Syariah Bukopin Periode 2011-2019 - Rizkia Ramadhani; Aas Nurasyiah; Suci Aprilliani Utami (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2021)
In 2019, Bank Syariah Bukopin obtained the lowest profitability value which is proxied by Return On Assets. Therefore, the bank needs to improve its health condition so that the bank can make a profit or profit as expected. This study aims to determine the effect of bank soundness on the level of profitability (ROA) of Bank Syariah Bukopin in 2011-2019. The research method used in this research is quantitative descriptive method with multiple linear regression analysis techniques. The population in this study is Bank Syariah Bukopin and the sample used in this study is Bank Syariah Bukopin in 2011-2019. The dependent variable in this study is profitability (ROA), while the independent variables in this study are the level of financing risk (NPF), the level of liquidity risk (FDR), the level of cost efficiency (BOPO), and the level of capital adequacy (CAR). The results showed that NPF, FDR, BOPO, and CAR had a significant simultaneous effect on profitability (ROA). As for partially, NPF has a negative and insignificant effect on ROA, BOPO has a significant negative effect on ROA, while CAR and FDR have no significant effect on ROA. The implication of this research is that banks need to maintain health conditions by preventing problematic financing, reducing operational costs, and using capital effectively and efficiently so that banks can obtain profitability as expected.